The taxation of municipal bonds : an economic appraisal - Mussa, Michael; Kormendi, Roger C. (Washington : American Enterprise Institute for Public Policy Research, 1979)
This book provides an in-depth investigation on issues surrounding the tax treatment of state and local bonds.
With a foreword
Bibliography: p. 225-228.
osc 9/6/17
Loans
Keywords: Municipal bonds; Taxation; United States